Review: Effect of Sexual Violence in Appearance of Post Traumatic Stress Disorder (PTSD) - Ja'far Mirzaei; Mohammad Reza Khodaei; Parvaneh Mohammadkhani (University of Social Welfare and Rehabilitation Sciences, 2007)
The familial violence is any violent action based on sexual dispute that result in somatic, sexual or psychiatric hurts or pain. One of the familial violence is child and spouse abuse that result in depression, anxiety and PTSD. The aim of this article is study of familial violence phenomena from different psychiatric and social views and the rate of appearance and epidemiology and clinical character of PTSD as the result of sexual rape. This study is based on review of literature and antecedent & internal and external investigations from 1989 to 2004 from internet sites like NC PTSD psychilt - psych Info. Conclusions of different accidental and nonaccidental studies sign the rate of 25 - 30% psychiatric side effects as the result of somatic and sexual abuse and appearance of PTSD-Depression and Anxiety. Because the phenomena of familial and sexual violence has social and psychiatric nature, It is necessary to take health care and educative and preventive methods for prevention of appearance of such injuries in society and support from familial and social network.